CONCEPTION RATES AFTER CERVICAL INSEMINATION OF FRESHLY DILUTED SEMEN AND CHILLED SEMEN IN NELLORE SHEEP (JODIPI) - KUMAR, P VISHAL; BRAMHAIAH, VEERA; RAJESH, M M; EKAMBARAM, B (The Indian Journal of Animal Reproduction, 2020)
This study was undertaken to evaluate the conception rate of Nellore sheep (Jodipi) with fresh diluted semen (0h) and chilled semen at 24 and 48h (stored at 5pC). Semen was collected, diluted with Tris Citric acid Fructose Yolk diluent and stored at 5pC for 24 and 48h to undertake cervical artificial insemination at natural estrus. The overall conception rates with diluted semen (0h) and chilled semen stored for 24 and 48 h based on 25 day non return rates were 61.90, 47.62 and 42.86 %, respectively. Therefore, it was concluded that spermatozoa are able to maintain their fertilizing ability at 5ºC up to 48 h and artificial insemination can performed with optimum conception rates.